2023
DOI: 10.1007/s00127-023-02482-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural transphobia is associated with psychological distress and suicidality in a large national sample of transgender adults

Abstract: Purpose Transgender adults face increasingly discriminatory laws/policies and prejudicial attitudes in many regions of the United States (US), yet research has neither quantified state-level transphobia using indicators of both, nor considered their collective association with transgender adults’ psychological wellbeing, hindering the identification of this potential social determinant of transgender mental health inequity. Methods We therefore used factor analysis to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…The passage of laws and policies that stigmatize groups can be a unique stressor to group members. A well-developed literature has established direct and indirect ways that structural stigma impacts LGBTQ+ people (e.g., Hatzenbuehler, 2016;Horne, Johnson, et al, 2022a;Price et al, 2021Price et al, , 2023. Scholars have also documented how responses to stressors are not uniform for all members of stigmatized groups (Patterson et al, 2020;Rao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The passage of laws and policies that stigmatize groups can be a unique stressor to group members. A well-developed literature has established direct and indirect ways that structural stigma impacts LGBTQ+ people (e.g., Hatzenbuehler, 2016;Horne, Johnson, et al, 2022a;Price et al, 2021Price et al, , 2023. Scholars have also documented how responses to stressors are not uniform for all members of stigmatized groups (Patterson et al, 2020;Rao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have pointed out that experiences and the impacts of structural stigma may not be felt the same for all members of a minoritized group (Patterson et al, 2020;Rao et al, 2020). Various dimensions of power and marginalization intersect with sexual and gender minority status, such that LGBTQ+ people may be differentially exposed to and uniquely impacted by structural stigma, including anti-LGBTQ+ legislation and associated political discourse (Flores et al, 2018;Grzanka et al, 2020;Meyer et al, 2011;Price et al, 2023;Schlehofer et al, 2023). Educational and financial privilege, for example, may allow some LGBTQ+ parents to reside in more progressive communities and/or send their children to more progressive schools, where attitudes and norms deviate significantly from and are more accepting than state laws or policies (Goldberg et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Journal of Youth and Adolescence, 52(10), 2012-2030. https://psycnet.apa.org/doi/10.1007/s10964-023-01818-2 sexual identity and gender identity development are deeply intertwined for many people (Hereth et al, 2020). For transgender people, gender identity development is often complicated by structural anti-transgender stigma Price et al, 2023), which encourages people to repress gender identities that do not match sociocultural expectations for the sex they were assigned at birth, even at the level of their own awareness (Hereth et al, 2020). Accordingly, to the extent that sexual and gender identity development are intertwined, sexual identity awareness might occur on a later timeline for transgender people relative to cisgender people.…”
Section: Subgroup Differences In Developmental Milestone Timing and P...mentioning
confidence: 99%
“…Journal of Youth and Adolescence, 52(10), 2012-2030. https://psycnet.apa.org/doi/10.1007/s10964-023-01818-2 others to experience adverse interpersonal experiences, such as victimization, in structurally stigmatizing contexts , with potential implications for structural stigma's association with sexual identity developmental milestones. Further, some LGB subgroups may be further impacted by additional sources of structural stigma such as structural transphobia characterized by laws and policies that fail to protect the rights of transgender people (Price et al, 2023). In addition, past studies have demonstrated differences in developmental milestones across gender and sexual identities.…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal minority stressors, such as overt cisheterosexist discrimination, have a direct effect on the mental health of SGM people (Bostwick et al, 2014; Lattanner et al, 2022). Research also suggests that structural stigma, such as anti-SGM laws and state-level attitudes, have a direct effect on the mental health of SGM people (Hatzenbuehler et al, 2009; Pachankis & Bränström, 2018; Pachankis et al, 2021; Price et al, 2023).…”
Section: Minority Stress Theorymentioning
confidence: 99%